The Influence of Word of Mouth on Purchase Decisions at Tokopedia - Dewantara, Yuni Putri (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The digital economy continues to drive the development of buying and selling from conventional to using e-commerce. Indonesian people have the highest number of e-commerce users in the world, namely 88.1% of internet users shop online at marketplaces. Based on Tokopedia's reputation which is still in second place in terms of usage in the community, several efforts can be made to encourage the use of Tokopedia as a superior marketplace. In accordance with several previous studies, one of the efforts is to promote word of mouth which can encourage increased purchasing decisions, in this case the Tokopedia marketplace by the general public. This study aims to determine the effect of word of mouth on purchasing decisions at Tokopedia. This research uses quantitative research methods with causal associative research types. The data collection method in this study was a survey through questionnaires distributed using Google form media. The population in this study is Indonesian society in general. The sampling technique in this study was a purposive sampling method with a total of 80 respondents. The data analysis method in this study is simple linear regression using SPSS 26 which involves 1 independent variable and 1 dependent variable. Based on the results of research on 80 respondents, the results show that there is a significant and strong influence between word of mouth on purchasing decisions at Tokopedia.